Blunt innominate artery trauma requiring repair and carotid ligation. (December 2017) - Howe, Kathryn L.; Guirgis, Mina; Woodman, Grant; Victor Chu, F.; Cooper, M.J.; Rapanos, Theodore; Szalay, David
Abstract: Traumatic dissection of the innominate artery is a rare clinical entity. Management of a patient with motorsensory compromise and dissection extending to the subclavian and right common carotid arteries is quite rare and can be quite involved. Here we present such a case and discuss the unique peri-operative decision-making in the context of what is reported in the literature. Restoration of motorsensory function is critical and in this case, requiring a multi-disciplinary team.